ANALYSIS OF SLANG WORDS FOUND IN MOVIE “SPIDER-MAN: NO WAY HOME” - Khofifah, Indar (ID Solutions, 2023)
Abstract – Slang words become the part of daily conversation. But it also occurs in the conversation of a movie. This study tries to find out the types of slang and the meaning of slang in the film “Spider-Man: No Way Home”. The theory proposed by Kipfer and Chapman (2007) to analyse the types of slang, and the theory proposed by Leech (1981) to analyse the types of meaning. This study used qualitative method. Regarding the first objective, there are two types of slang words found in this film, such as primary slang and secondarv slang. The occurrence of primary slang dominates the type of slang used in this film, because speakers can make this type of slang easy for people to understand. Referring to the secand object, which classifies 7 tvpes of meaning, namely conceptual, connotative, social, affective, reflected, collocative and thematic.